Who deserves to be the finfluencer? - Eneng Nur Hasanah; Deddy P. Koesrindartoto; Sudarso Kaderi Wiryono; Agnes Enya Angelica (Journal of Open Innovation: Technology, Market and Complexity)
Financial influencers (finfluencers) are prevalent across various social media platforms, addressing a wide range of financial topics tailored to audience needs. In response to this phenomenon, this study examines the characteristics and content strategies of the top nine finfluencers on TikTok, YouTube, and Instagram, with a particular focus on their potential impact on investor behavior. Employing a mixed-methods approach, this research explores eight key dimensions: finfluencer’s power, interactivity, content quality, character, collaboration, advertising strategies, content packaging, and credibility. The findings indicate that financial investment topics dominate the content landscape, with a strong emphasis on promoting specific stocks, cryptocurrencies, and other investment products. Despite their growing popularity, the study identifies a significant gap, as most finfluencers lack formal education or certification in finance, raising concerns about the dissemination of misinformation and the potential for risky investment advice. Furthermore, the analysis highlights the diverse roles assumed by finfluencers, including independent investors and traders, financial planners, and frugal living advocates. These roles significantly shape their ability to convey financial knowledge and influence the investment decisions of their audiences. This study also underscore the need for stricter regulatory oversight by financial authorities and enhanced accountability mechanisms on social media platforms, where transparency from finfluencers is crucial in ensuring ethical practices and fostering audience trust, particularly concerning financial decision-making. Finally, this research represents the first in-depth study to systematically analyse financial content on social media through a comprehensive content analysis approach.